A Study on Outcome of Early Caffeine Administration in Very Preterm Neonates - Dr Basavaraj; Hareesh Sanikam; Pavan Pujar; Anjali R; Pushpalatha K (Asian Journal of Clinical Pediatrics and Neonatology, 2019)
Background: Apnea intervals frequently occur in very preterm infants. Methylxanthenes stimulate breathing efforts and hence have been used for treating apnea of prematurity. Aim: to study the outcome of early caffeine administration in very preterm neonates. Subjects and Methods: The first (1st) group babies received early caffeine within 48 hours of life before developing apnea. The second group (2nd) group babies received caffeine late after 48 hours, after onset of apneic episode. Results: There was no significant difference in the number of episodes of apnea, bradycardia and hypoxemia. Also no significant difference in the incidence of Patent ductus arteriosus (PDA), Intra ventricular hemorrhage (IVH), Necrotizing enterocolitis (NEC), Retinopathy of prematurity (ROP) or Bronchopulmonary dysplsia (BPD). Conclusion: There was no significant difference noted in the number of episodes of apnea, bradycardia and hypoxemia in the group with early caffeine administratration compared to late caffeine administration.